Advances in applied digital human modeling and simulation : proceedings of the AHFE 2016 International Conference on Digital Human Modeling and Simulation, July 27-31, 2016, Walt Disney World®, Florida, USA /: proceedings of the AHFE 2016 International Conference on Digital Human Modeling and Simulation, July 27-31, 2016, Walt Disney World®, Florida, USA. ([2016]) - Unknown
No abstract available